ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2013)
The purpose of this study is to investigate and analyze the effect of Cash Ratio, Growth, Firm Size, Return on Assets (ROA), Debt to Total Assets (DER), and the Debt to Equity ratio of the Dividend Payout Ratio (DPR) on the manufacturing companies listed on Indonesia Stock Exchange (BEI) for the period 2009-2011. This study uses 30 manufacturing companies listed on the Indonesia Stock Exchange. The sample selection is done using purposive sampling method. The data used are secondary data obtained from the website www.idx.co.id and Indonesian Capital Market Directory (ICMD). The data collected will be analyzed by the method of data analysis to prior classical assumption test before testing the hypothesis. Testing the hypothesis in this study using multiple linear regression with t test. T test aims to determine the effect of independent variables on the dependent variable partially. The results showed that the variable Cash Ratio, Firm Siz, Debt to Equity ratio have positive and not significant effect on Dividend Payout Ratio (DPR), the variable Growth, Debt to total assets have negative and significant effect on Dividend Payout Ratio (DPR), while the variable Return on Assets (ROA) have positive and significant impact on Dividend Payout Ratio (DPR). Keywords: Cash Ratio, Growth, Firm Size, Return on Assets (ROA), Debt to Total Assets, Debt to Equity ratio, Dividend Payout Ratio (DPR)